Effect of a Mental Health Mobile App on Depression Symptom Reduction - Sri Ariyanti; Lie Jie; Cai Jixiong (Yayasan Adra Karima Hubbi, 2024)
Mobile health applications are increasingly being used as a tool to manage mental health conditions, particularly depression. These apps provide accessible and scalable interventions, such as cognitive behavioral therapy (CBT) exercises and mood tracking, allowing users to engage in self-guided treatment. However, the effectiveness of such apps in reducing depression symptoms, particularly over extended periods, remains under-researched. This study aimed to evaluate the effectiveness of a mental health mobile app in reducing depression symptoms over a 12-week period. The primary goal was to determine if consistent use of the app leads to significant improvements in mental health compared to traditional in-person therapy. A randomized controlled trial (RCT) was conducted with 200 participants diagnosed with mild to moderate depression. Participants were randomly assigned to two groups: the intervention group used the mobile app, and the control group received standard in-person therapy. Depression symptoms were assessed at baseline, 6 weeks, and 12 weeks using the Patient Health Questionnaire-9 (PHQ-9). Engagement with the app, such as logins and completed CBT exercises, was also tracked for the intervention group. The intervention group showed a 35% reduction in PHQ-9 scores by the 12-week mark, while the control group exhibited a 20% reduction. Higher app engagement correlated with greater symptom reduction. The mobile app proved particularly effective in reducing depression symptoms among those who consistently used its features. The mental health mobile app was effective in significantly reducing depression symptoms, especially with regular use. These findings support the use of mobile apps as a complementary or alternative treatment to traditional therapy for managing depression.